PENGGUNAAN METODE PETA KONSEP DITAMBAH DENGAN MEDIA LEAFLET UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN SISWA KELAS IX DI SMP NEGERI 1 KAMBERA - Pilu, Redemta Oktaviani Ubini; Makaborang, Yohana; Ndjoeroemon, Yohana (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2025)
Background Education is the basis of national intelligence and one of the important needs for society, because education and humans are interrelated. Through education, humans can gain more knowledge and understanding of all aspects of life. Methods: The type of research used in this research is classroom action research. This research was carried out at SMP Negeri 1 Kambera in class VIII A science subjects and this research was carried out in the odd semester of the 2023/2024 academic year and carried out according to the learning schedule in August 2024. The population in this research was all students in class VIII of SMP Negeri 1 Kambera in the odd semester of the 2023/2024 academic year and the sample in this research was all 32 students in class VIII D. Results: In the pre-cycle, student learning results showed an average cognitive score of 71.25, with 75% of students not yet reaching the Minimum Completeness Criteria (KKM). The average student psychomotor score is 64.65, with 66% of students not meeting the KKM. In cycle I, after applying the mind mapping method and leaflet media, the students' average cognitive score increased to 80.31, with 69% of students meeting the KKM. Psychomotor learning outcomes in cycle I also increased, with an average of 77 and 66% of students reaching the KKM. In cycle II, the application of this method showed better results, with an average cognitive score of 91.2 and 84% of students meeting the KKM. Psychomotor scores in cycle II reached an average of 86.91, with 84% of students meeting the KKM Conclusion: The application of the mind mapping method equipped with leaflet media can improve student learning outcomes, both in the cognitive and psychomotor domains